Impacto en Colombia de la Lex Mercatoria (2006)
This test proposes to analyze of the phenomenon of the new Lex Mercatoria and to evaluate its probable assimilation in the Colombian normative system. Leaving to a side the theoretical debates on the existence or not of the new Lex Mercatoria, as well as the debates trims in its legitimacy or convenience, part of a transdisciplinaria reading of Legal Sciences, supported in other sciences like the Economy or the International Relations. With this intention the old Lex Mercatoria like medieval antecedent of the present Lex studies. Later one analyzes the structural me of the New Lex from his conceptualización, sources, characteristics, actors and causes that promote it at international level. Finally is approaches the assimilation in Colombia of the International Sale of Goods Convention of the Nations United, the Principles of Unidroit, Uniform Customs and Practices for Documentary Credits and some jurisprudences.